APPLICATION OF THE X-RAY STRUCTURE ANALYSIS FOR IMPROVEMENT OF TECHNOLOGICAL PROCES- SES OF WIRE PRODUCTION AT BMZ - D. V. Kuznetsov; I. V. Schetinin; T. P. Kurenkova; E. S. Seryogina; A. V. Demidov (Литьë и металлургия)
The X-ray diffraction methods of qualitative and quantative analysis of phase composition of the brass coating, scale on the surface of brass wire, rod, patented wire, methods of determining the characteristics of the microstrains the lattice ferritic matrix pearlitic high-carbon steel, are explored.